STEAM Approach to Students' Critical Thinking Ability on the Concept of Sound Waves for Developing PBL Model Learning Tools - Yulianti Kohohon; Mursalin; Muhammad Yusuf; Masri Kudrat Umar; Tirtawaty Abdjul; Ritin Uloli (Jurnal Penelitian Pendidikan IPA, 2023)
One learning model that supports improving critical thinking skills and developing 21st century education is the PBL model. This research aims to describe the quality of the STEAM approach-based PBL model learning tools development for Students' Critical Thinking Ability on the concept of sound wave using the ADDIE development model. The results of the validation carried out by three validators obtained an average percentage for the learning implementation plan of 93.08%, student activity sheets of 92.58%, teaching materials of 90.82%, and critical thinking tests of 92.72%, and all included in the very valid criteria. The practicality of learning tools is seen from learning implementation of 90.72% with excellent criteria, the student's response to the learning tools was very positive with the ease aspect percentage of students' responses was 86.67%, the enthusiasm aspect percentage of 93.33%, the motivated aspect percentage of 86.67% and the involvement aspect percentage of 83.33%. The effectiveness of learning tools in student activity of 91.67% with excellent criteria, the results of the critical thinking test increased by 49.00%, from previously the overall average score of students was 30.33% to 79.33% and the effectiveness category through the N-Gain test was 0.71 with high criteria